Religious tourism and the environment - Shinde, Kiran A.; Olsen, Daniel H. 1973- (Wallingford, Oxfordshire Boston, MA CABI, 2020)
The environmental impacts of religious tourism / Kiran A. Shinde, Daniel H. Olsen -- Pilgrimage, religious tourism, biodiversity, and natural sacred sites / Daniel H. Olsen -- Managing the environment in religious tourism destinations : a conceptual model / Kiran A. Shinde -- Human sanctuaries can be created everywhere : pilgrimage, tourism, and conservation in Vrindavan, India / Joshua Nash -- The Beyul : Sherpa perspectives on landscapes characteristics and tourism development in Khumbu (Everest), Nepal / Sanjay K. Nepal, Yang Mu, Po-Hsin Lai -- Religious tourism and environmental conservation in Lumbini, the birthplace of Lord Buddha, World Heritage Site, Nepal / Anouk Lafortune-Bernard, Rajendra, N. Suwal, Kai Weise, Robin A.E. Coningham -- Interreligious dialogue : trees, stones, water, and interfaith ritual experiences in Lebanon / Nour Farra Haddad -- Mimicking mountains : Antoni Gaudí's Sagrada Família and the mountain of Montserrat / Josep-Maria Garcia-Fuentes -- Disease and health-related issues at mass religious gatherings / Daniel H. Olsen -- The natural environment and waste management at the Hajj / Jahanzeeb Qurashi -- The effects of natural disasters on religious tourism sites : earthquakes in the spiritual heart of Italy / Michael Di Giovine, Elisa Ascione -- Religion, the environment, and sacred places : lessons learned and future directions / Daniel H. Olsen, Kiran A. Shinde
"This is the first book to discuss both religious tourism and the environment. Moving beyond the documentation of impacts, it examines intersections between the two areas, such as the environment as a resource or generator of religious tourism. Chapters discuss such important topics as disease, environmental responsibility and host perspectives"--
Includes bibliographical references and index
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Tourism -- Religious aspects; Pilgrims and pilgrimages; Tourism -- Environmental aspects